Penggunaan Model Pembelajaran Eksperiensial (Experiential Learning) untuk Meningkatkan Minat Belajar Siswa pada Mata Pelajaran Biologi - Nuraeni, Siti; Karmana, I Wayan (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2025)
The use of innovative learning media can increase students' interest in learning a material. One interesting solution that can be applied is the use of experiential learning models. This study aims to analyze the use of experiential learning models in increasing the interest in learning of class X students at SMA Negeri 8 Mataram in biology subjects. This study uses the Classroom Action Research (CAR) method. This Classroom Action Research was carried out in two cycles, with each cycle consisting of four stages, namely planning, implementation, observation, and reflection. Data collection techniques were in the form of questionnaires. The results of the study showed that in cycle I, the average student interest in learning reached 81%, this is included in the category of very high student interest in learning when using the experiential learning model. While in cycle II, the average student interest in learning reached 83%, this is included in the category of very high student interest in learning when using the experiential learning model. Thus, it can be concluded that the use of experiential learning models contributes significantly to increasing students' interest in learning biology at SMA Negeri 8 Mataram.